2009
DOI: 10.1200/jco.2009.27.18_suppl.lba4505
|View full text |Cite
|
Sign up to set email alerts
|

ESPAC-3(v2): A multicenter, international, open-label, randomized, controlled phase III trial of adjuvant 5-fluorouracil/folinic acid (5-FU/FA) versus gemcitabine (GEM) in patients with resected pancreatic ductal adenocarcinoma

Abstract: LBA4505 Background: Adjuvant 5-FU/FA (ESPAC-1 trial) and GEM (CONKO-001 trial) provide improved survival for patients with resected pancreatic cancer compared to no chemotherapy. The aim of the ESPAC-3 (v2) trial was to compare 5FU/FA vs GEM to identify if either adjuvant chemotherapy was associated with a significantly better survival. Methods: Patients with an R0/R1 resection for pancreatic ductal adenocarcinoma were randomized (stratified for resection margin status and country) <8 weeks of surgery to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…This was statistically non-significant that may be because 55% of cases were in stage IIB and 27.5% with positive safety margin 15 . The ESPAC-3 trial resulted in median OS of 23 months in cases treated with fluorouracil/folinic acid, while those treated with gemcitabine had a median OS of 23.6 months 16 . The aforementioned, both were less than OS obtained in our CTH group attributed to advanced stage of disease as 55% of cases with stage IIB, 27.5% with positive margin and 30% with elevated CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…This was statistically non-significant that may be because 55% of cases were in stage IIB and 27.5% with positive safety margin 15 . The ESPAC-3 trial resulted in median OS of 23 months in cases treated with fluorouracil/folinic acid, while those treated with gemcitabine had a median OS of 23.6 months 16 . The aforementioned, both were less than OS obtained in our CTH group attributed to advanced stage of disease as 55% of cases with stage IIB, 27.5% with positive margin and 30% with elevated CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials supported the use of chemotherapy in radically resected patients, but the most effective regimen (gemcitabine or 5-fluorouracil/leucovorin) remains unclear (7,8). Similarly a phase 3 trial showed that a cisplatin-epirubicin-5-fluorouracil-gemcitabine regimen obtained a 1-year survival rate of 38.5%, which was significantly better than single-agent gemcitabine (6).…”
Section: Discussionmentioning
confidence: 99%
“…Although several attempts have been made to increase the survival using combinations of chemotherapy and targeted therapy, only a marginal success was achieved with gemcitabine combined with capecitabine or erlotinib, and with a four-drug regimen (4)(5)(6). According to the results of CONKO-001 and ESPAC-3 trials (7,8), gemcitabine also increased the disease-free survival (DFS) and overall survival (OS) in the adjuvant setting. However, the most effective adjuvant chemotherapy remains unclear, and the 5-year survival in patients undergoing resection still hovers between 10% and 20% (1).…”
Section: Introductionmentioning
confidence: 99%
“…The ESPAC group recently reported data from ESPAC-3 in their latest abstract, showing equivalence of gemcitabine and 5-FU plus leucovorin as adjuvant therapy, with a better safety profile in favor of gemcitabine [53]. ESPAC-4 has now been launched comparing gemcitabine with gemcitabine plus capecitabine in the adjuvant setting because the assessment of the ESPAC group is that CRT offers no benefit in this setting.…”
Section: Adjuvant Crt In Pancreatic Adenocarcinomamentioning
confidence: 99%